Quality of Service at Taman Safari and Tourist Satisfaction - Awaloedin, Dipa Teruna; Azfa, Muhamad; Hasanudin, Hasanudin; Pradini, Gagih (Peneliti.net, 2024)
Taman Safari Indonesia is a popular tourist destination located in Cisarua, Bogor, offering visitors the unique experience of observing wildlife up close in an educational setting. As one of Indonesia's premier attractions, the quality of service at Taman Safari Indonesia plays a significant role in visitor satisfaction. This study employs a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to identify the strengths, weaknesses, opportunities, and threats facing Taman Safari Indonesia. The analysis reveals that Taman Safari Indonesia's strengths lie in its diverse collection of animals, comprehensive facilities, strategic location, and engaging educational concept. However, challenges include relatively high ticket prices, weekend traffic congestion, facilities in need of upgrades, and a limited variety of shows. Opportunities for growth involve the development of digital tourism, partnerships with external parties, and enhanced educational tourism. Threats encompass competition from other tourist destinations, risk of natural disasters, climate change, and economic downturns. The conclusions drawn from this SWOT analysis indicate that Taman Safari Indonesia has the potential to continue growing, but it must address both internal and external challenges. Several recommendations for increasing its appeal and service quality include adding more show variety, expanding digital tourism content, upgrading facilities, and offering more attractive tour packages. These measures are expected to enhance visitor satisfaction and help Taman Safari Indonesia maintain competitiveness amid rising competition